Molecular mechanisms of memory consolidation, reconsolidation, and persistence - Merlo, Emiliano (2015)
In the last decades there have been significant advances in our understanding of the cellular and subcellular mechanisms underlying changes in synaptic connectivity that subserve memory formation. The so called Theory of Synaptic Plasticity and Memory has gathered a wealth of experimental support from different areas of neuroscience to become the main phenomenological description of memory at the behavioural level. This special issue of neural plasticity compiles some of the most recent advances in our understanding of the mechanisms underlying formation and persistence of different types of memories from invertebrates to humans. Contributions from different laboratories around the world pinpoint hot topics in this area of memory research, highlighting growing avenues for future research.